Presidential Election Campaign of the Republic of Indonesia via Twitter (X) - Wildanu, Eka; Nauli Fitri Agasya, Hesti (Jurnal Polisci, 2024)
The number of Twitter (X) users in Indonesia is 24 million people, ranked 5th in the world. Twitter tweets color the 2024 presidential election. The presidential candidate has a large Twitter following, along with his popularity. Prabowo has 4.5 million, Anies 4.5 million, and Ganjar 2.6 million followers on Twitter. Supporters of the presidential candidate can campaign with tweets to convey the programs and ideas of the presidential candidate they support to attract the sympathy of other Twitter readers. Twitter applies specific policies, namely paid political promotion posts. The policy includes rules banning the promotion of fake content and content that can potentially undermine public trust in elections. Twitter also created a global advertising transparency center so users can track political ads on the platform. This policy change is said to impact the 2024 election significantly. Twitter is also currently creating a team overseeing safety and election policies to combat manipulation of the election content, display inauthentic accounts, and monitor threats that may appear on the platform.